Examining millennials' online gambling behavior: a comparison of generational differences. (2nd October 2017) - Suh, Eunju; Alhaery, Matt; Abarbanel, Brett; McKenna, Andrew
Abstract : Purpose: This study aims to examine Millennials and generational differences in online gambling activity by comparing online gambling behavior across four different generations: Silent Generation, Baby Boomers, Gen Xers and Millennials. Design/methodology/approach: The sample comprised tracked gambling data at the individual player level provided by an online casino accepting real money wagers in a major US gambling market. Attributes of gambling behavior were examined and compared across different generations using Kruskal–Wallis test and pairwise comparisons. Findings: Generational differences were observed in 13 of the 16 behavioral variables. Millennials spent the least amount of time on gambling and exhibited the lowest scores on the number of days for slot gambling, trip length and trip frequency among all generations. However, their average table gaming volume per play day was greater than those of other generations. Practical implications: The results of this study provide a better understanding of the generational differences in online gambling behavior. They also help casino operators and gaming machine manufacturers develop casino games and products that can appeal to different generational groups in the online gambling market. Originality/value: Despite the on-going industry discussion about Millennials and their potential influence on the online gambling market, there appears to be a paucity of empirical research on the online gambling behavior of the Millennial generation. This study fills that gap in empirical evidence, addressing generational differences in online gambling.